The energy cost of the tonoplast futile sodium leak - Shabala, Sergey; Chen, Guang; Chen, Zhong-Hua; Pottosin, Igor (The New phytologist, 2020)
Active removal of Na⁺ from the cytosol into the vacuole plays a critical role in salinity tissue tolerance, but another, often neglected component of this trait is Na⁺ retention in vacuoles. This retention is based on an efficient control of Na⁺-permeable slow- and fast-vacuolar channels that mediate the back-leak of Na⁺ into cytosol and, if not regulated tightly, could result in a futile cycle. This Tansley insight summarizes our current knowledge of regulation of tonoplast Na⁺-permeable channels and discusses the energy cost of vacuolar Na⁺ sequestration, under different scenarios. We also report on a phylogenetic and bioinformatic analysis of the plant two-pore channel family and the difference in its structure and regulation between halophytes and glycophytes, in the context of salinity tolerance.